BIOTECHNOLOGY FOR ENERGY PRODUCTION: CONSTRUCTION OF A MICROBIAL FUEL CELL USING THE INDUS RIVER SEDIMENT SOIL AND WATER COUPLED WITH THEIR MICROBIAL FLORA - Hayat, Muhammad Qasim; Qudsia, Syeda (European Scientific Journal, ESJ, 2014)
Current study provides new openings for the sustainable generation of energy by using Microbial Fuel Cells (MFCs) biotechnology. We constructed a MFC using the Indus River sediment soil and water with their microbial flora without adding any additional chemical source of energy. In resulted MFC, voltage readings were observed and their significance is calculated statistically. Furthermore, based on present findings we have proposed a microbial fuel generator model for the Indus River in Pakistan, which can be executed any where in the world.